ІННОВАЦІЙНА ПОЛІТИКА ДЕРЖАВИ (Світ фінансів, 2017)
Стефанів І. Ф. Інноваційна політика держави. Висвітлено основні засади формування інноваційної політики держави. З’ясовано критерії ефективності реалізації інноваційних систем. Окреслено напрямки удосконалення державного регулювання у сфері інновацій та інноваційної політики держави. Stefaniv I. An innovative policy of the state is on the modern stage. Basic principles of forming of the state innovative policy are investigated. The effi ciency criteria of realization of the innovative systems are found out. Directions of improvement of government control in the innovations fi eld are formed.